Evaluation of banking performance in Algeria using the camels model. Case study of the National Bank of Algeria in the period 2015-2023 - thameur, oussama; bissar, abdelhakim (Journal of Research in Finance and Accounting, 2023)
This research aims to evaluate the financial performance of the National Bank of Algeria using the CAMELS model during the period 2015 to 2021, which is one of the most important methods used by the banking sector to assess financial risks and financial performance and maintain its stability, as several different indicators such as capital adequacy and asset quality were used Management efficiency, profitability quality, liquidity, and sensitivity to market risks. The arithmetic mean was also used to determine the bank's rating and determine its financial performance during the study years. The results of the study indicate that there are some weaknesses in the National Bank of Algeria, especially with regard to the liquidity index. Where the bank obtained the third rating, i.e. “average”, according to the CAMELS rating model.